Gain‐of‐function mutations in SMAD4 cause a distinctive repertoire of cardiovascular phenotypes in patients with Myhre syndrome. Issue 10 (14th June 2016) - Lin, Angela E.; Michot, Caroline; Cormier‐Daire, Valerie; L'Ecuyer, Thomas J.; Matherne, G. Paul; Barnes, Barrett H.; Humberson, Jennifer B.; Edmondson, Andrew C.; Zackai, Elaine; O'Connor, Matthew J.; Kaplan, Julie D.; Ebeid, Makram R.; et al.
Abstract : Myhre syndrome is a rare, distinctive syndrome due to specific gain‐of‐function mutations in SMAD4 . The characteristic phenotype includes short stature, dysmorphic facial features, hearing loss, laryngotracheal anomalies, arthropathy, radiographic defects, intellectual disability, and a more recently appreciated spectrum of cardiovascular defects with a striking fibroproliferative response to surgical intervention. We report four newly described patients with typical features of Myhre syndrome who had (i) a mildly narrow descending aorta and restrictive cardiomyopathy; (ii) recurrent pericardial and pleural effusions; (iii) a large persistent ductus arteriosus with juxtaductal aortic coarctation; and (iv) restrictive pericardial disease requiring pericardiectomy. Additional information is provided about a fifth previously reported patient with fatal pericardial disease. A literature review of the cardiovascular features of Myhre syndrome was performed on 54 total patients, all with a SMAD4 mutation. Seventy percent had a cardiovascular abnormality including congenital heart defects (63%), pericardial disease (17%), restrictive cardiomyopathy (9%), and systemic hypertension (15%). Pericarditis and restrictive cardiomyopathy are associated with high mortality (three patients each among 10 deaths); one patient with restrictive cardiomyopathy also had epicarditis. Cardiomyopathy and pericardial abnormalities distinguish Myhre syndrome from other disorders caused by mutations in the TGF‐β signaling cascade (Marfan, Loeys–Dietz, or Shprintzen–Goldberg syndromes). We hypothesize that the expanded spectrum of cardiovascular abnormalities relates to the ability of the SMAD4 protein to integrate diverse signaling pathways, including canonical TGF‐β, BMP, and Activin signaling. The co‐occurrence of congenital and acquired phenotypes demonstrates that the gene product of SMAD4 is required for both developmental and postnatal cardiovascular homeostasis. © 2016 Wiley Periodicals, Inc.